Avaliação da remoção de cor e desinfecção de lixiviados de aterro sanitário utilizando ozônio e peróxido de hidrogênio - Seewald, Marina Medtler (Universidade do Vale do Rio dos Sinos, 2013)
Degradation of grounded waste in landfill generates a liquid with high pollution potential characterized by its dark color, high concentration of organic matter and ammonia nitrogen. Landfill leachate may still contain pathogenic microorganisms from wastes contaminated by human excreta, presenting health risk. For treating landfill leachate, biological processes have shown good performance, especially in organic matter removal. However, in order for the removal efficiency to attain local legislation, particularly in older leachate, a post treatment is necessary. Use of advanced oxidation processes has shown efficiency in color removal, destruction of pathogens and increased biodegradability of recalcitrant effluents. The purpose of this study is to evaluate color removal and disinfection of landfill leachate using ozone and hydrogen peroxide as oxidizing agents. Therefore, twelve experiments were performed in AOP system treating raw and treated leachate by pond system. Six tests were conducted with ozone only and six combining ozone and hydrogen peroxide. The POA was operated with volume of 460L and tests were carried out for 96h. The ozone (gas) concentration was 29 mg/L and hydrogen peroxide (liquid solution added) was 1000 mg/L in the leachate. Characterization of landfill leachate generated in São Leopoldo showed high variability. Therefore, to discuss results of color removal, groups of tests were created using like criteria true color concentration. Although attained results indicated similarity between tested oxidants, performed ANOVA two factors with repeated measures showed difference between oxidizing agents used in color removal. Hydrogen peroxide outperformed ozone alone. True color removal occured faster with smaller true color concentrations. The disinfection of the leachate, using ozone combined with hydrogen peroxide showed higher inactivation rates of fecal coliforms. Turbidity and organic matter in the leachate did not prevent the disinfection. All tests reached over 90% efficiency in true color removal at 96h and over 92% efficiency in disinfection within 24h.
Evaluation of color and disinfection of landfill leachate using ozone and hydrogen peroxide
Keywords: Lixiviado; Cor; Coliformes termotolerantes; Ozônio; Peróxido de hidrogênio; Processos oxidativos avançados; Leachate; Color; Fecal coliforms; Ozone; Hydrogen peroxide; Advanced oxidation process; ACCNPQ::Engenharias::Engenharia Civil